2010
DOI: 10.1111/j.1600-0897.2010.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Semen in HIV‐1 Transmission: Inhibitor or facilitator?

Abstract: Citation Doncel GF, Joseph T, Thurman AR. Role of semen in HIV‐1 transmission: inhibitor or facilitator? Am J Reprod Immunol 2011; 65: 292–301 Sexual transmission of human immunodeficiency virus type 1 (HIV‐1) accounts for 60‐90% of new infections, especially in developing countries. During male‐to‐female transmission, the virus is typically deposited in the vagina as cell‐free and cell‐associated virions carried by semen. But semen is more than just a carrier for HIV‐1. Evidence from in vitro and in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 77 publications
0
40
0
3
Order By: Relevance
“…Semen is more than a mere carrier of HIV-1, since it contains many biological factors that may facilitate or inhibit HIV-1 transmission 41 . For instance, semen neutralizes the acidic cervical mucus increasing HIV-1 diffusion 42 otherwise trapped in mucus 43 .…”
Section: Semen Affects Hiv Acquisitionmentioning
confidence: 99%
“…Semen is more than a mere carrier of HIV-1, since it contains many biological factors that may facilitate or inhibit HIV-1 transmission 41 . For instance, semen neutralizes the acidic cervical mucus increasing HIV-1 diffusion 42 otherwise trapped in mucus 43 .…”
Section: Semen Affects Hiv Acquisitionmentioning
confidence: 99%
“…Previous in vitro studies have shown that human semen enhances HIV-1 infectivity independent of tropism (1)(2)(3)(4). Some investigations suggest a proinflammatory role when semen is introduced to the genital tract such that it alters the activation state of potential target cells and neutralizes the native acidic pH (5). Still, findings presented elsewhere suggest a target cell-specific protective effect of semen (6)(7)(8)(9).…”
mentioning
confidence: 91%
“…The sites of inflammation are enriched with HIV target immune cells and may have breaches in the mucosal epithelial barrier, both of which facilitate HIV acquisition [4]. Seminal plasma (SP) is the main vector for HIV in sexual transmission, but SP is not only a carrier for HIV [5,6]. In vitro studies have shown that SP may both inhibit and facilitate HIV infection.…”
Section: Introductionmentioning
confidence: 99%